Clinical and Ultrasonographic Aspects of Benign and Malignant Mammary Tumors in Female Dogs - Brandão Guedes, Paula Elisa; Bandeira Thame Daniel, Hannah; Oliveira Rosa Sampaio, Kátia Moema; Barboza da Silva, Elizângela; Ferreira, Manoel Luiz; Lima de Lavor, Mário Sérgio; de Oliveira Clark, Rosana Maria; Wenceslau, Amauri Arias; Abou Said, Roueda; Lessa Silva, Fabiana (Acta Scientiae Veterinariae, 2020)
<span style="font-size: 12pt; font-family: 'Times New Roman'; background-color: transparent; font-weight: bold; font-style: italic; font-variant-numeric: normal; font-variant-east-asian: normal; vertical-align: baseline; white-space: pre-wrap;">Background<span style="font-size: 12pt; font-family: 'Times New Roman'; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; vertical-align: baseline; white-space: pre-wrap;">: Mammary neoplasms in dogs are commonly observed in veterinary clinical routine, most of which being malignant. Hormonal stimulation, endogenous or exogenous, may possibly influence its development. In addition to clinical evaluation, ultrasound analysis can provide information about the characteristics of breast lumps. The association between clinical-epidemiological and pathological data is important for diagnosis. Therefore, given the importance of this pathology for the health of affected dogs, we aimed to evaluate the clinical and ultrasound alterations, along with the factors associated with the development of benign and malignant mammary neoplasms in female dogs. <span style="font-size: 12pt; font-family: 'Times New Roman'; background-color: transparent; font-weight: bold; font-style: italic; font-variant-numeric: normal; font-variant-east-asian: normal; vertical-align: baseline; white-space: pre-wrap;">Materials, Methods & Results<span style="font-size: 12pt; font-family: 'Times New Roman'; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; vertical-align: baseline; white-space: pre-wrap;">: We examined 47 samples from the mammary tumors of 35 female dogs at the Small Animal Clinic of the Veterinary Hospital (HV) of the Santa Cruz State University (UESC). The dogs underwent a complete clinical examination, with clinical staging, via TNM classification, followed by hematological, biochemical, radiological and ultrasound, abdominal, and breast exams. Breast ultrasound examination was used to evaluate the shape parameters such as, limits, margins or contour, ecotexture, echogenicity, hyperechoic halo, posterior acoustic shading, surrounding changes, and nodule components. These criteria were associated with the histopathological classification of neoplasms. Epidemiological data was studied through an adapted questionnaire containing information on risk factors associated with breast cancer. The same questionnaire was applied to tutors of 19, age-matched, female dogs with no history of breast cancer. The results revealed that most female dogs with neoplasia were over eight years of age, with no specific breed and were not castrated, and 31.4% of them had already been administered with contraceptives during the reproductive period. Ovariohysterectomy acted as a protective factor (OR 0.06) to the development of breast tumors, while contraceptive use was considered as a risk factor (OR 6.99). The average time reported between tumor perception and clinical care was 13.2 months. The caudal and inguinal abdominal breasts were the most affected. Among the samples evaluated, 76.6% were malignant, with mixed tumor carcinoma being the most frequent type and 69.4% graded in grade I. Nodules classified as malignant showed the largest diameter (<span style="font-size: 12pt; font-family: 'Times New Roman'; background-color: transparent; font-style: italic; font-variant-numeric: normal; font-variant-east-asian: normal; vertical-align: baseline; white-space: pre-wrap;">P < 0.05). Breast ultrasound results revealed that tumors with heterogeneous echotextures and mixed components were associated with malignancy (<span style="font-size: 12pt; font-family: 'Times New Roman'; background-color: transparent; font-style: italic; font-variant-numeric: normal; font-variant-east-asian: normal; vertical-align: baseline; white-space: pre-wrap;">P < 0.05). <span style="font-size: 12pt; font-family: 'Times New Roman'; background-color: transparent; font-weight: bold; font-style: italic; font-variant-numeric: normal; font-variant-east-asian: normal; vertical-align: baseline; white-space: pre-wrap;">Discussion<span style="font-size: 12pt; font-family: 'Times New Roman'; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; vertical-align: baseline; white-space: pre-wrap;">: The fact that the average age of female dogs with breast cancer was over eight years of age corroborates the literature. Considering that a greater age would mean a longer exposure to the carcinogenic initiators responsible for mutations, and to promoters, such as hormonal changes. Contraceptives increase the risk of breast lumps, while reduce that of ovariohysterectomy, in female dogs, even when performed after the second heat. The size of the nodules and ultrasound criteria related to echotexture and the type of component of the neoplasia may be used as prognostic parameters of female breast nodules. Additionally, most nodules evaluated in this study were malignant (mixed tumor carcinoma was the most common subtype), possibly due to the owners' delay in seeking veterinary care after tumor observation. Although malignant, most nodules presented with a low histopathological grading. Background: Mammary neoplasms in dogs are commonly observed in veterinary clinicalroutine, most of which being malignant. Hormonal stimulation, endogenous or exogenous,may possibly influence its development. In addition to clinical evaluation, ultrasound analysiscan provide information about the characteristics of breast lumps. The association betweenclinical-epidemiological and pathological data is important for diagnosis. Therefore, given theimportance of this pathology for the health of affected dogs, we aimed to evaluate the clinicaland ultrasound alterations, along with the factors associated with the development of benignand malignant mammary neoplasms in female dogs.Materials, Methods & Results: We examined 47